2019
DOI: 10.17850/njg99-4-3
|View full text |Cite
|
Sign up to set email alerts
|

A Silurian age for the metasedimentary rocks of the Ekne Group, Trøndelag, Mid-Norwegian Caledonides: and inferences for a peri-Laurentian provenance

Abstract: ICP-MS) of detrital zircons from low-grade metasandstones, some tuffaceous, of the biostratigraphically-barren Ekne Group in the Støren Nappe of the Mid-Norwegian Caledonides have revealed that the sequence is almost entirely of Silurian age. The complete Ekne Group succession is about 2800 m thick and estimates of maximum depositional age based on the mean age of the youngest five zircon grains show an upward younging from 446.6 Ma at the base of the group to 432.9 -427.2 Ma in the upper half. In the sample c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Based on the age data provided in Stokke et al (2018), Roberts et al (2019) suggested that the Skuggliberga unit may correlate with the Ekne Group northeast of Trondheim (Fig. 1A).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the age data provided in Stokke et al (2018), Roberts et al (2019) suggested that the Skuggliberga unit may correlate with the Ekne Group northeast of Trondheim (Fig. 1A).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…1A). Four detrital zircon samples from the Ekne Group are dominated by Palaeozoic detrital zircons which show main peaks at 460-450 Ma, interpreted by Roberts et al (2019) to indicate deposition in the Late Ordovician to Silurian. However, the Ekne Group is lithologically different from the Skuggliberga unit, as it is dominated by turbiditic sandstones and siltstones and does not contain volcanic rocks.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The Scandian Caledonides in Greenland and Baltica are a good example of a hard collision that resulted in a bivergent orogenic wedge. The pro-wedge preserves Taconic deformed rocks and upper plate arc rocks in the highest east-directed nappes in western Nor-way (Roberts et al 2007(Roberts et al , 2019, whereas west-directed nappes of the retro-wedge occur in eastern Greenland (Higgins et al 2004). The nappe stack in the Swiss-Italian Alps comprises penetratively deformed and metamorphosed rocks of both the lower European as well as the upper Adrian plates, elegantly illustrated and described in the kinematic-geometric evolutionary reconstructions made by Escher and Beaumont (1997).…”
Section: Hard Collisionmentioning
confidence: 99%